Craneofaringiomas: cirugía transnasal via endoscópica - Ajler, Pablo; Castro Barros, Fabian; Massa, Daniela (Revista Argentina de Neurocirugía, 2020)
Introduction: Due to its anatomical location, craniopharyngiomas are difficult tumors to treat. Complete resection has high morbidity and mortality and if a partial resection is chosen, the recurrence is common. According to their suprasellar extension and its relationship with stalk, it can be classified into: preinfundibular, transinfundibular and retroinfundibular. Objetive: The aim of this video is to describe the surgical technique we use for preinfundibular craniopharyngioma.Methods: We review a preinfundibular craniopharyngioma operated on the Neurosurgery Department of the Hospital Italiano de Buenos Aires, through a transnasal endoscopic approach.Results: Total removal was achived, no acute complications were found such as diabetes insipidus or cerebrospinal fluid leak and improved their visual field.Conclusion: Craniopharyngioma surgery requires detailed knowledge of skull base anatomy and approaches. The use of endoscopy has allowed better access to this type of lesions, reducing comorbidities and patient hospital stay. Complete resection with low morbidity are the treatment of this tumors.
Keywords: Craniopharyngiomas; Endoscopic Transnasal Approach; Skull Base; Orbitozigomatic